1985
DOI: 10.1002/bip.360240606
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Boc‐Leu‐Aib‐Pro‐Val‐Aib‐Aib‐Glu(OBzl)‐Gln‐Phl × H2O, the C‐terminal nonapeptide of the voltage‐dependent ionophore alamethicin

Abstract: SynopsisBoc-L-Leu-Aib-Pro-Val-AibAibGlu(OBz1)-Gln-Phl (Boc = t-butyloxycarbonyl, Aib = a-aminoisobutyric acid, Bzl = benzyl, Phl = phenylalaninol), C59H,Nlo0,,, the protected C-terminal nonapeptide with the sequence 12-20 of alamethicin, crystallize: in the orthorhombic space group P2,2121 with a = 15.666, b = 16.192, c = 26.876 A, and 2 1 4. The molecular conformation is right-handed helical with three a45 + 1 hydrogen bonds) and three p-turns (4 -1 hydrogen bonds). All but two of the hydrogen bonds are signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 39 publications
1
26
1
Order By: Relevance
“…The columns of head-to-tail-bonded helices must necessarily pack in a parallel fashion. This parallel packing of the a-helices is in contrast to the antiparallel packing generally observed in proteins and in other small a-helical structures (9)(10)(11).…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…The columns of head-to-tail-bonded helices must necessarily pack in a parallel fashion. This parallel packing of the a-helices is in contrast to the antiparallel packing generally observed in proteins and in other small a-helical structures (9)(10)(11).…”
contrasting
confidence: 78%
“…Although peaks for many other H atoms also were found in difference maps, idealized calculated positions were used for all the H atoms on C atoms. Least (10) 7379 (10) 10443 (9) 9193 (11) 10069 (9) 8425 (8) 8591 (4) 8129 (5) 7861 (6) 7516 (5) 8259 (4) 6898 (4) 6549 (5) 7583 (4) 5545 (5) 6899 (4) 5921 (5) 7064 (4) 5552 (3) 6294 (3) 4122 (5) 7069 (4) 4008 (5) 8236 (4) 4142 (6) 9102 (5) 3992 (5) 10050 (4) 3692 (6) 9816 (4) 3382 (7) 10503 (5) 3120 (9) 10040 (6) 3100 (8) 8902 (7) 3388 (7) 8225 (5) 3697 (5) 8683 (4) 6704 (4) 8085 (3) 7076 (5) 8282 (4) 7916 (5) 7480 (4) 7858 (4) 7189 (3) 7773 (6) 9541 (4) 7888 (7) 9801 (5) 9140 (7) 9916 (5) 6573 (9) 9580 (6) 8715 (4) 7143 (3) 9511 (5) 6381 (4) 8629 (5) 5241 (4) 8908 (4) 4756 (3) 10432 (6) 6226 (5) 7529 (4) 4788 (3) 6536 (5) 3712 (4) 5974 …”
mentioning
confidence: 99%
“…Instead, hydrogen bonds are observed between the N1, N2, 07, and 08 atoms of the peptide (not involved in the intramolecular hydrogenbonding scheme; see Fig. 1) and the cocrystallized solvent (11) 3122 (14) 3348 (13) 2549 (13) 1381 (14) 1194 (14) 2644 (13) 1784 (8) 3798 (10) 4059 (11) 3680 (14) 5442 (11) (13) 1238 (10) 935 (9) 878 (12) 1275 (13) 1204 (7) 1393 (8) 1343 (9) 410 (11) 1549 (9) 1958 (9) 1801 (6) 2707 (8) 3390 (10) 3838 (11) 4024 (10) 3087 (8) 3490 (6) 2446 (8) 2019 (14) 2709 (12) 1274 (13) 1833 (10) 1777 (8) 1730 (9) 1546 (12) 734 (10) 1766 (14) 2223 (11) 2007 (6) 3006 (8) (12) 3999 (9) 3313 (19) 3513 (17) 2668 …”
Section: Resultsmentioning
confidence: 99%
“…More recently, by theoretical (7)(8)(9)(10)(11) as well as experimental (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) investigations, it has been shown that the 4,q, angles ofthe achiral a-aminoisobutyric acid residue (Aib), the prototype of Caa-dialkylated a-amino acids, are restricted to values near those associated either with right-or left-handed a-or 310-helices, unless it is part of a strained cyclic compound (28). The x-ray diffraction structures of aaminoisobutyric acid homopeptides to the pentamer have provided examples of short (less than two complete turns) 310-helical conformations in the solid state (14,15,22,23).…”
mentioning
confidence: 99%
“…Helical peptides (with more than 6 residues) in crystals have almost always been observed to pack in a head-to-tail motif that results in forming long rods or columns of helices throughout the crystal (Bosch et al, 1985a(Bosch et al, , 1985bFrancis et al, 1985;Marshall et al, 1990). In crystals where the succeeding a-helices in a column are in good register with respect to each other, 3 intermolecular NH.…”
Section: Head-to-tail Hydrogen Bondingmentioning
confidence: 99%